Efektivitas Pelaksanaan Program Rehabilitasi dan Rekonstruksi Pasca Bencana Gempa Bumi oleh Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Pasaman Barat di Kenagarian Kajai - Azirahmah, Havenda; Putri, Nora Eka (Lembaga Yasin AlSys, 2025)
This study aims to analyze the effectiveness of the post-earthquake rehabilitation and reconstruction program implemented by the Regional Disaster Management Agency (Badan Penanggulangan Bencana Daerah or BPBD) of West Pasaman Regency in Kenagarian Kajai. The 2022 earthquake caused significant damage to homes, infrastructure, and public facilities, necessitating a rapid and appropriate recovery response. The study employed a quasi qualitative approach with a simple research design to evaluate program implementation, identify obstacles, and formulate improvement recommendations. Data were collected through interviews, observation, documentation, and the distribution of 96 questionnaires, and analyzed based on effectiveness indicators: target accuracy, timeliness, and outcome achievement. The findings show that the program was relatively ineffective, with a performance score of 73%. The program included the repair of severely damaged houses, construction of public facilities, and restoration of road access. However, several challenges were identified, such as limited human resources, delays in fund disbursement due to complex bureaucracy, and inaccurate damage assessments leading to unequal aid distribution. Despite these issues, the program’s positive impact was still felt by the community, though its effectiveness needs improvement. The study recommends strengthening inter-agency coordination, accelerating fund disbursement processes, enhancing human resource capacity, and improving data collection systems to ensure more accurate and equitable aid distribution. These findings are expected to serve as a reference for future post-disaster rehabilitation and reconstruction policy development.